Today I feel silly & other moods that make my day - Curtis, Jamie Lee, 1958-; Cornell, Laura (New York, N.Y. : HarperCollinsPublishers, 1998)
A child's emotions range from silliness to anger to excitement, coloring and changing each day.
"Joanna Cotler books."
Adult 250
Accelerated Reader AR
Keywords: Emotions -- Juvenile fiction; Stories in rhyme